Hipoxemia silenciosa y uso de oxímetro de pulso en el hogar para detección precoz de complicaciones por Covid-19: reporte de un caso y revisión de la literatura - Berna L, Valentina; Mendoza I, Laura (Revista Hospital Clínico Universidad de Chile, 2021)
Silent hypoxemia is one of the clinical presentations caused by SARS-CoV-2. It is still considered a medical mystery, as there are inconsistencies between arterial oxygen saturation levels and respiratory symptoms; a clinical scenario that had not been seen before. Their main risk is that it delays medical assistance because they do not have breathing difficulties and, when they consult, the lung damage is quite advanced. The early detection of hypoxia can favor the premature diagnosis of COVID-19 pneumonia and start treatment without delay. The pulse oximeter is presented as a useful, inexpensive, and easy-to-use tool for monitoring oxygen saturation at home in mild illness and detecting silent hypoxemia. This work presents the case of a patient with COVID-19 who, thanks to the use of a pulse oximeter at home, was able to detect silent hypoxemia and favored the early diagnosis of SARS-CoV-2 pneumonia.